The cardioprotective role of beta-blockers in patients with diabetes mellitus. - Landray, M; Toescu, V; Kendall, M (2002)
This paper reviews the role of beta-blockers in the prevention of cardiovascular morbidity and mortality in patients with diabetes mellitus. There is good evidence from randomized controlled trials that beta-blockers, in particular the lipophilic agents, substantially reduce cardiovascular mortality and morbidity. However, hitherto beta-blockers have been underused in diabetic patients, perhaps because of perceived risks of beta-blocker therapy. Reappraisal of the evidence suggests that the traditional reluctance to use beta-blockers in this group is based on fears of adverse effects that are largely unfounded.